Posts: 102
Threads: 20
Joined: Dec 2012
Reputation:
0
As the topic say this is for mathematics genius
You have to prove one equation in 12 hours. After that i will announce the answer. However will prove this first i will give him +rep(if it is not the against of rep rule system).
So the equation is:
Prove:-
Study = Fail
Posts: 757
Threads: 36
Joined: Jun 2013
Reputation:
0
Prove:
We know that,
study= no fail ...... (1)
no study= fail ...... (2)
By adding equation 1 & 2 we get,
study+no study=no fail+fail
or, study(1+no)=fail(no+1)
or, study(1+no)=fail(1+no)
Now, by dividing (1+no) from both sides, we get,
study = fail
So, if you study, you will fail!
Posts: 1,690
Threads: 18
Joined: Jul 2012
Reputation:
0
Study = fail
Let the word be fail as a fail.
When we divide fail/study, Fail wins because when you study you will fail.
Apply this a2+b2=A and B
Fail2+Study2= Fail and Study
.'.Fail= Fail
;Study= Study
Hence proved.
Posts: 353
Threads: 36
Joined: Apr 2011
Reputation:
0
Expand the following:
(a+b)=2
( a + b ) = 2
( a + b ) = 2
Etc
Hence expanded.
Posts: 4,878
Threads: 85
Joined: Jun 2007
Reputation:
0
So,
fail usually is a zero as it describes the absence of success or any valueable effect.
Now, as study isnt a general term, but rather describes a series of all different kinds of studying, lets name a single element of that series as study(x), where x Є N is indexing the elements. Assuming that study represents the intellectual gain as a number, study(x) Є Z might be positive or negative for all indexes.
now as study isnt a single number, but a series, you cant compare it with fail, which is a single number.
Following the standards the meaning of the equation would then rather be
Σ (x Є N) (study(x)) = fail = 0
Now using general knowledge, for any kind of study, there must be another study with the opposite effect, e.g. one study teaches you something, another one teaches the first one was wrong, so it has the inverted fain of the first study. Meaning
(FOR ALL) x Є N: Ǝ y Є N: study(x) = -study(y)
Using full induction you can now always find a pair of elements in study that nullify each other, proving that
Σ (x Є N) (study(x)) = 0 = fail
so
study=fail